Description of Nitrincola elmenteitensis sp. nov.; a haloalkaliphilic bacterium isolated from Lake Elmenteita in Kenya - Romano, Mwirichia; Hamadi, Boga (African Science Publications, 2020)
A bacterial strain designated E-48T was isolated from Lake Elmenteita, an alkaline saline lake within the East African rift valley. The cells were Gram-negative, motile, non-spore forming rods. Growth was observed at a pH range between 6.0 and 13.0 (optimum pH 9.5), salt concentration (w/v) up to 20% (optimum 5%) and the temperature for growth was between 14.0-44°C (optimum temperature 36°C). On the basis of 16S rRNA gene sequence similarity (99%), strain E-48T belonged to the genus Nitrincola (family Oceanospirillaceae, class Gammaproteobacteria). The DNA GC content was 46.4 mol%. The major cellular fatty acid was the mono-unsaturated 18:1 ω7c while the major isoprenoid quinone was Q-8. However, at the genome level, strain E-48T had a G+C difference of 7.17% from the genome of N. lacisaponensis DSM 16316T. Based on the various characteristics, it is proposed that the isolate represents a new species within the genus Nitrincola for which the name Nitrincola elmenteitensis is proposed. The type strain is E-48T (=DSM 26266T=LMG 28382T).
Keywords: Nitrincola, Gamaproteobacteria, Soda Lakes